Análise quali-quantitativa da operação de colheita mecanizada de café em duas safras - Santinato, Felipe; da Silva, Rouverson Pereira [UNESP]; Cassia, Marcelo Tufaile [UNESP]; Santinato, Roberto (My University, 2014)
The mechanized harvest of coffee is a technology used in many coffee plantations in order to increase the efficiency, reduce the time spent and reduce the cost of operation. To ensure that the harvest has good results are necessary the adequate regulation of the rods vibration of the machine as a function of variety, productivity, stage of maturity of the fruits and the conditions under which farming of coffee. This study aimed to evaluate the mechanized harvest of coffee (Coffea arabica L.), analyzing the behavior of two sides of the machine under two frequencies of vibration of rods in high and low production crops. The evaluations were performed in Patos de Minas (Minas Gerais State, Brazil), in farm with coffee's cultivars Red Catucaí arranged in circular planting, beig sampled 40 plots in a factorial (2 × 2). Were used a Jacto KTR harvester working with 750 and 950 rpm frequency. It follows that for the year with negative biannuality the right side of the machine harvested 35% more than the left side. The use of the greatest vibration didn't increase the collection efficiency and led to a higher defoliation by 14% the vibrating operation with less intensity. For high crop year the left side of the machine let more than 48% coffee on the ground than the right side and the different frequencies of vibration, the higher promoted more efficiency in harvest efficiency without increase damage in the plants.
Quality of operation of harvesting of coffee at two crops
Keywords: Coffea arabica L; Harvesting loses; Rod vibration